Učinek šesttedenskega programa 'Zdrave vadbe ABC' na moč odraslih - Pori, Maja (Šport (Ljubljana), 2014)
The aim of the paper was to analyse the effects of the Healthy workout ABC - program A on inactive adults. The sample consisted of 12 physically inactive adults, all residents of the town Žiri. The sample represented volunteers of average age of 43.5 years (SD = 10.5 years). The subjects represented the control group (they were measured six weeks prior to the start of exercising and immediately before the start and after the exercising) as well as the experimental group. The subjects exercised twice a week under professional supervision. They carried out the ćHealthy workout ABC. To check the effects of the exercise, we used 6 strength tests of UKK test battery. The effect of the exercise was tested with the analysis of variance for repeated measurements. The results showed statistically significant changes in 5 strength tests. The highest positive change was obtained in tests of strength endurance. Since strength exercises should be part of every healthy workout it would be therefore advisable for the inactive adult population to participate in healthy workouts similar to ABC.
Keywords: healthy workouts; inactive people; nedejavni ljudje; physical activity; telesna dejavnost; zdrava vadba